Entrepreneurial intention in Madagascar's rural areas: The predictive role of the theory of planned behaviour - Ratsimanetrimanana, Fenosoa (My University, 2018)
In Madagascar, a country ranked among the poorest in the world, the major type of entrepreneurship encountered, particularly in rural areas, is a form of self-employment, where individuals, by obligation, decide to create their own job, not for the sake of pursuing opportunity-based entrepreneurship, but to secure livelihood. Subsequently, as the need to be self-employed presupposes intention, this thesis examined the Theory of Planned Behaviour (TPB) as a predictive model in the formation of entrepreneurial intention (El) among the self-employed, in a rural under-researched context. More specifically, through a deductive approach, this study aimed to verify the predictive role of TPB, in its entirety. This was done through the formation process of El and measuring the influence of cognitive variables and psychological factors (counterfactual thinking, dispositional optimism, entrepreneurial alertness) and the contextual factor (access to finance) on the relationship between TPB dimensions and El in Madagascar's rural areas, where gender and level of education could play a role. The purpose underpinning the research was actualized through adopting a cross-sectional survey. The population object of the research was a sample of 1 500 self-employed individuals living in Madagascar's rural areas, obtained through cluster sampling with a quota. The research instrument used was an interview questionnaire consisting of five separate sections, with items inspired by those that have been successfully tested in the frameworks of similar previous work. The research was nonexperimental and adopted either a regression mechanism or a bootstrap method to establish the causal relationship between the variables under study. The results of the study reveal that the predictive role of TPB, in its entirety, with regard to El, was observed only among the male group of respondents. The level of education did not influence the TPB, in its entirety, in predicting El. The relationship between the attitude towards behavior dimension and El was slightly moderated by dispositional optimism and entrepreneurial alertness. Among the overall respondents, cognitive counterfactual thinking, dispositional optimism, and entrepreneurial alertness moderated faintly the relationship between the subjective normal dimension and El. Page The relationship between the perceived behavioral control dimension and El was a little moderated by cognitive counterfactual thinking, dispositional optimism, and entrepreneurial alertness within the overall group of respondents. Access to finance weakly moderated the relationship between cognitive variables and El. Through the thesis, an opportunity to contribute to the advancement of the TPB model emerged when the moderate effects of cognitive variables and psychological factors, as well as the contextual factor, are accounted for with regard to the relationship between TPB dimensions and El. This approach allowed for the expansion of the theory by integrating more contextualized concerns. At a practical level, the thesis suggested that cognitive variables and psychological factors as well as the contextual factor, as antecedents to El, need to be nurtured to stimulate increased entrepreneurial initiatives within an environmental context relevant to women, comprising of the design, development and delivery of entrepreneurial training, mentoring, and incubation programs. For future investigations, it would be interesting to scrutinize how cultural dimensions might influence the relationship between TPB dimensions and El.
Submitted in partial fulfilment of the requirements of the degree of Doctor of Philosophy in Management, Graduate School of Business Faculty of Commerce, Law, and Management University of the Witwatersrand
Keywords: Madagascar; Theory of Planned Behavior; Entrepreneurial intention